Characterization based on biomechanical properties for meniscus scaffolds by sonication decellularization treatment - Norzarini, A.; Kitajima, Tatsuo; Feng, Zhonggang; Sha'ban, Munirah; Noor Azmi, Azran Azhim (American Scientific Publishers, 2017)
onication decellularization treatment ability to efficiently decellularize meniscus tissues requires proper evaluations. The purpose of this study is to investigate the maintenance of biomechanical properties within meniscus scaffolds. In sonication decellularization treatment, tissue samples were sonicated at 40 kHz ultrasound frequency in 0.1% sodium dodecyl sulfate (SDS) for 10 h. For control, an immersion treatment by 0.1% SDS was applied in the absence of ultrasonic exposure. Cell removal efficiency was determined through a histological analysis of van Gieson staining. The treatment effects on viscoelastic properties that are crucial for scaffolds strength were properly studied. Extracellular matrix (ECM) properties were determined through Picrosirius red and Safranin-O/Fast green staining. The decellularized tissues were further evaluated by scanning electron microscopy (SEM) for its ultrastructure. The findings demonstrated a complete nuclei removal in sonication-treated tissues compared to immersion-treated tissues. Viscoelastic properties, namely stiffness, compression, and residual force were maintained after the sonication decellularization treatment. The maintenance of viscoelastic properties was supported by ECM preservation that is mainly composed of collagen and GAG contents. An ultrastructure observation showed the presence of micropores on the surface of sonication-treated tissues. The micropores are determined as chondrocytes lacunae that conserve chondrocytes within it. Sonication decellularization treatment is thus capable of preparing the meniscus scaffolds candidate in which the biomechanical strength of tissues is maintained by preserving the ECM properties. © 2017 American Scientific Publishers. All rights reserved.